2019
DOI: 10.1002/ccr3.2075
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde aortic approach for atrial fibrillation ablation with a conventional 3‐D mapping catheter: A case report

Abstract: Key Clinical Message The presence of a Gore‐Tex patch can create difficulty in performing transeptal puncture for atrial septal defect patients underwent atrial fibrillation ablation. The maneuverability and stability of using manually operated catheters via retrograde aortic approach could be overcome by a large‐curved catheter to form a loop facilitating approachability to all parts of left atrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Though complete LA mapping was not feasible, a senior operator could reach the left interatrial septum via a transaortic approach with satisfactory catheter contact and stability. This retrograde approach has been successfully adopted in previous reports, 5 but hemodynamic consequences might occur with simultaneous catheter crossing through the aortic and mitral valves. Moreover, caution should be taken since excessive catheter manipulation or looping using this unusual approach might damage the aortic or mitral valve apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though complete LA mapping was not feasible, a senior operator could reach the left interatrial septum via a transaortic approach with satisfactory catheter contact and stability. This retrograde approach has been successfully adopted in previous reports, 5 but hemodynamic consequences might occur with simultaneous catheter crossing through the aortic and mitral valves. Moreover, caution should be taken since excessive catheter manipulation or looping using this unusual approach might damage the aortic or mitral valve apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…This retrograde approach has been successfully adopted in previous reports, 5 but hemodynamic consequences might occur with simultaneous catheter crossing through the aortic and mitral valves. Moreover, caution should be taken since excessive catheter manipulation or looping using this unusual approach might damage the aortic or mitral valve apparatus.…”
Section: Left Atrial (La) Access and Mappingmentioning
confidence: 99%
“…6,7 However, this system can be used in only limited institutions. Recently, Comandante et al 8 reported the first case of atrial fibrillation ablation through a retrograde approach with conventional irrigating ablation catheter and 3D electroanatomic mapping. To stabilize the catheter position and to facilitate approachability to all parts of the LA, they used a large curve catheter to form a loop.…”
Section: Discussionmentioning
confidence: 99%